1984
DOI: 10.1111/j.1365-2125.1984.tb02555.x
|View full text |Cite
|
Sign up to set email alerts
|

Failure of ‘therapeutic’ doses of beta‐adrenoceptor antagonists to alter the disposition of tolbutamide and lignocaine.

Abstract: The effects of separate 1 week pre‐treatments with each of the beta‐ adrenoceptor antagonists, propranolol (80 mg every 12 h), metoprolol (100 mg every 12 h) and atenolol (50 mg once daily), on the disposition of a single i.v. dose of tolbutamide were studied in six healthy volunteers. In addition, the effects of a 1 week pre‐treatment with metoprolol (100 mg every 12 h) and atenolol (50 mg once daily) on the disposition of orally and i.v. administered lignocaine were determined in seven healthy subjects. Tolb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Whereas Conrad et al (1983) showed that metoprolol lowered the clearance of lignocaine significantly by about 25%, more recent studies found no significant effects (Jordo et al, 1984;Miners et al, 1984). However, it is possible that the power of these studies was not sufficient to detect the predicted small decrease in the clearance of lignocaine due to enzyme inhibition.…”
Section: Discussionmentioning
confidence: 95%
“…Whereas Conrad et al (1983) showed that metoprolol lowered the clearance of lignocaine significantly by about 25%, more recent studies found no significant effects (Jordo et al, 1984;Miners et al, 1984). However, it is possible that the power of these studies was not sufficient to detect the predicted small decrease in the clearance of lignocaine due to enzyme inhibition.…”
Section: Discussionmentioning
confidence: 95%
“…Available evidence from interaction studies indicates that β‐adrenoceptor antagonists [110], dextropropoxyphene [111], diltiazem [112], enoxacin [113], erythromycin [81, 114], metronidazole [115], olanzapine [116] and omeprazole [117, 118] are all unlikely to inhibit CYP2C9 activity in vivo .…”
Section: Factors Affecting Cyp2c9 Activitymentioning
confidence: 99%
“…For example, the various pathways of theophylline metabolism were shown to be induced by rifampicin, sulphinpyrazone and cigarette smoking, inhibited by propranolol and cimetidine and unaffected by sulphaphenazole 2–4 . While also induced by rifampicin, tolbutamide metabolic clearance was, in contrast, inhibited by sulphinpyrazone and sulphaphenazole and unaffected by cigarette smoking, propranolol and cimetidine 5–7 . In the course of these studies, an individual was identified whose tolbutamide metabolic clearance was only 15% of the population mean 8 .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] While also induced by rifampicin, tolbutamide metabolic clearance was, in contrast, inhibited by sulphinpyrazone and sulphaphenazole and unaffected by cigarette smoking, pro-pranolol and cimetidine. [5][6][7] In the course of these studies, an individual was identified whose tolbutamide metabolic clearance was only 15% of the population mean. 8 Despite impaired tolbutamide elimination, indices of metabolic clearance for theophylline and debrisoquine, the latter known to exhibit genetic polymorphism, were close to the respective population averages.…”
Section: Introductionmentioning
confidence: 99%